Pengaruh Penempatan Dan Disiplin Kerja Terhadap Kinerja Kerja Anggota PNTL Di Pusat Pendidikan Dan Pelatihan Kepolisian (Pusdiklat) Timor Leste - Miguel Amaral Pires da Silva; Pius Bumi Kellen; Mateus Ximenes (RELASI : JURNAL EKONOMI, 2023)
This study was conducted to determine the effect of job placement and discipline on job performance. The data population for this survey is 78 members of the Education and Training Center in Dili Timor Leste. 100% of this survey uses quantitative data with data collection methods using This survey uses SPSS tools. Research results show that 1) Placement has a positive and significant effect on work performance 2) Work discipline has a positive and significant effect on work performance 3) Placement and Discipline Work simultaneously affects the performance of members in PUSDIKLAT Dili East Timor.